An integrative review of supportive relationships between child‐bearing women and midwives - Hadeer Almorbaty; Lyn Ebert; Eileen Dowse; Sally Wai‐Chi Chan (Wiley, 2023)
Abstract Aims To review and evaluate the literature on the factors related to developing supportive relationships between women and midwives, including facilitators and barriers. Design An integrative review. Method The search used CINAHL, MEDLINE, Embase, EMcare, Maternity and Infant Care, PsycINFO, and Google Scholar from January 2009-June 2020. Two reviewers screened the eligible studies, and 2,399 records were identified. Quality was assessed with the mixed methods appraisal tool, and 14 articles were included. Results The findings highlight that successful relationships require therapeutic communication, trust, respect, partnership, and shared decision‐making. Supportive relationships improve women's satisfaction and birth outcomes, and continuity of care model is an enabling factor. Further research is required to understand supportive relationships in non‐continuity of care models and when different cultural backgrounds exist.